Construction safety risk drivers: A BIM approach. (February 2016) - Malekitabar, Hassan; Ardeshir, Abdollah; Sebt, Mohammad Hassan; Stouffs, Rudi
Highlights: Safety risk drivers convey information about potential accidents to the design phase. This paper derives 5 sets of safety risk drivers from analyzing 363 accident cases. An object oriented approach to the drivers makes them quantifiable by BIM software. Processing these drivers improves the identification of potential hazards up to 40%. Abstract: Automatic identification of construction safety issues using Building Information Models requires an understanding of the safety risk drivers that are detectable during the design phase. However, literature is scarce on risk identification tools and no set of drivers has been suggested to date to address construction accidents. Plenty of accidents do occur under circumstances that can be distinguished by analyzing project documents, but available BIM-based tools are currently limited to checking the clauses of safety standards. This research provides five sets of safety risk drivers that can influence either the probability or the consequences of an accident, the application of which helps identify more than 40% of potential fatalities in construction projects. The results reflect the design attributes and environmental conditions found playing a key role in the occurrence of 363 accidents reported by three different sources, and are associated with object oriented rules that are classified into four categories depending on how they are to be processed by rule checking engines. The so classified drivers can be checked to determine if safety risks are likely to arise in a project, while they maintain an acceptable level of comprehensiveness as BIM technologies progress.